Економіко-управлінські аспекти енергетичної ефективності суб’єктів господарювання в територіальних громадах - Перебийніс, В.І.; Рогоза, М.Є.; Безрук, Д.І.; Вітрюк, Н.М. (Вісник економічної науки України, 2023)
Уточнено теоретико-методологічні засади формування управління енергетичною ефективністю. Виокремлені поняття «енергетична ефективність технічних систем», «енергетична ефективність біологічних систем», «енергетична ефективність соціально-економічних систем», «енергетична ефективність суб’єкта господарювання», «енергетична ефективність територіальної громади». Встановлені види енергетичного ефекту територіальної громади. Визначена сутність понять «ефективність енергозаощадження територіальної громади» та «ефект енергозаощадження територіальної громади». Обґрунтовані види ефекту енергозаощадження територіальної громади. Сформовано матрицю потоку пального. Визначено функціональні складові процесу управління енергетичною ефективністю. Обґрунтовано напрями оптимізації енергетичних потоків в територіальних громадах. The theoretical and methodological principles of the formation of energy efficiency management have been clarified. The concepts of "energy efficiency of technical systems", "energy efficiency of biological systems", "energy efficiency of socio-economic systems", "energy efficiency of a business entity", and "energy efficiency of a territorial community" have been distinguished.
It has been proven that increasing the energy efficiency of economic entities in the context of territorial community development should not allow: deterioration of working conditions of economic entity's personnel and life safety of residents of communities (imperative of the human factor); complication of the ecological situation on the community territory (ecological imperative); reduction of economic efficiency of a business entity and well-being of the community population (priority of economic assessment).
The types of energy effect of the territorial community have been established. The essence of the concepts of "energy saving efficiency of territorial community" and "energy saving effect of territorial community" have been defined. The types of energy saving effect of the territorial community have been reasoned. The fuel flow matrix has been formed. The functional components of the energy efficiency management process have been defined.
The directions for optimization of energy flows in territorial communities have been substantiated as follows: the choice of energy supply enterprises; optimization of energy resource delivery routes; substantiation of energy-optimal sizes and structure of the transport fleet of territorial communities and oil industry (if available); optimization of storage stocks of energy resources and their management.